Safety and immunogenicity of RTS, S/AS01 malaria vaccine in infants and children with WHO stage 1 or 2 HIV disease: a randomised, double-blind, controlled trial. Issue 10 (October 2016) - Otieno, Lucas; Oneko, Martina; Otieno, Walter; Abuodha, Joseph; Owino, Emmanuel; Odero, Chris; Mendoza, Yolanda Guerra; Andagalu, Ben; Awino, Norbert; Ivinson, Karen; Heerwegh, Dirk; Otsyula, Nekoye; et al.
Summary: Background: Malaria remains a major global public health concern, especially in sub-Saharan Africa. The RTS, S/AS01 malaria candidate vaccine was reviewed by the European Medicines Agency and received a positive scientific opinion; WHO subsequently recommended pilot implementation in sub-Saharan African countries. Because malaria and HIV overlap geographically, HIV-infected children should be considered for RTS, S/AS01 vaccination. We therefore aimed to assess the safety of RTS, S/AS01 in HIV-infected children at two sites in western Kenya. Methods: We did a randomised, double-blind, controlled trial at the clinical trial sites of the Kenya Medical Research Institute (KEMRI)–Walter Reed Army Institute of research in Kisumu and the KEMRI/US Centers for Disease Control and Prevention in Siaya. Eligible participants were infants and children aged from 6 weeks to 17 months with WHO stage 1 or 2 HIV disease (documented positive by DNA PCR), whether or not they were receiving antiretroviral therapy (ART). We randomly assigned participants (1:1) to receive three doses of either RTS, S/AS01 or rabies vaccine (both 0·5 mL per dose by intramuscular injection), given once per month at 0, 1, and 2 months. We did the treatment allocation using a web-based central randomisation system stratified by age (6 weeks–4 months, 5–17 months), and by baseline CD4% (<10, 10–14, 15–19, and ≥20). Data were obtained in an observer-blind manner, and the vaccine recipient, their parent or carer, the funder, and investigators responsible for the assessment of endpoints were all masked to treatment allocation (only staff responsible for the preparation and administration of the vaccines were aware of the assignment and these individuals played no other role in the study). We provided ART, even if the participants were not receiving ART before the study, and daily co-trimoxazole for prevention of opportunistic infections. The primary outcome was the occurrence of serious adverse events until 14 months after dose 1 of the vaccine, assessed in the intention-to-treat population. This trial was registered atClinicalTrials.gov, numberNCT01148459 . Findings: Between July 30, 2010, and May 24, 2013, we enrolled 200 children to our study and randomly assigned 99 to receive RTS, S/AS01 and 101 to receive rabies vaccine. 177 (89%) of the 200 children enrolled completed 14 months of follow-up. Serious adverse events were noted in 41 (41·4%, 95% CI 31·6–51·8) of 99 RTS, S/AS01 recipients and 37 (36·6%, 27·3–46·8) of 101 rabies-vaccine recipients (relative risk 1·1, 95% CI 0·8–1·6). 20 (20·2%, 95% CI 12·8–29·5) of 99 RTS, S/AS01 recipients and 12 (11·9%, 6·3–19·8) of 101 rabies-vaccine recipients had at least one serious adverse event within 30 days after vaccination, mainly pneumonia, febrile convulsions, and salmonella sepsis. Five (5·1%, 95% CI 1·7–11·4) of 99 RTS, S/AS01 recipients and four (4·0%, 1·1–9·8) of 101 rabies-vaccine recipients died, but no deaths were deemed related to vaccination. Mortality was associated with five cases of pneumonia (1% RTS, S/AS01 recipients vs 3% rabies-vaccine recipients), five cases of gastroenteritis (3% RTS, S/AS01 recipients vs 2% rabies-vaccine recipients), five cases of malnutrition (2% RTS, S/AS01 recipients vs 3% rabies-vaccine recipients), one case of sepsis (1% rabies-vaccine recipients), one case of Haemophilus influenza meningitis (1% rabies-vaccine recipients), and one case of tuberculosis (1% RTS, S/AS01 recipients). Interpretation: RTS, S/AS01 was well tolerated when given to children with WHO clinical stage 1 or 2 HIV disease along with high antiretroviral and co-trimoxazole use. Children with HIV disease could be included in future RTS, S/AS01 vaccination programmes. Funding: GlaxoSmithKline Biologicals SA andPATH Malaria Vaccine Initiative .